Approaches to learning among school-aged youth in Nepal: Factor structure of learning behaviors scale scores. (June 2015) - Hamlet, Helen S.; Schaefer, Barbara A.; Herrick, Margaret; Rai, Renuka
Educational progress and advancement is essential to the social and economical growth in Nepal. With 2015 as the goal date for the Dakar Framework for Action, identification of methods to improve student outcomes is fundamental to this goal. Assessing student learning behaviors in order to strengthen and/or remediate a student's approach to learning facilitates academic achievement. The Learning Behaviors Scale (LBS) provides a behaviorally based assessment instrument for exploring students' behaviors in the classroom. This study investigated the factor structure, multidimensional structure, and item endorsement of the LBS for a sample of 223 school-aged Nepalese students. A four-factor structure was revealed for this population. The four factors represent: task approach; emotional negativity/ sojho ; task engagement/ thiken ; and self-control. In addition, two dimensions of learning behaviors emerge. These represent task approach and level of engagement. Finally, a comparative analysis of the data identified similarities between the US sample and the Nepalese sample. The results of this study indicate a pattern of learning behaviors, as identified by the LBS, which is similar across the two cultures.